MENINGKATKAN HASIL BELAJAR TARI SISWA DENGAN MENGGUNAKAN MEDIA AUDIOVISUAL DI KELAS VII SMP NEGERI 2 TANJUNG MUTIARA - Wulanda Khairunisa; Yuliasma Yuliasma; Desfiarni Desfiarni (FBS Universitas Negeri Padang, 2018)
Abstract This article aims to describe the improvement of student learning outcomes by using audiovisual media in dance art subjects at SMP Negeri 2 Tanjung Mutiara. The type of research was classroom action research carried out in 2 cycles. The subjects of the study were 7th-grade students of SMP Negeri 2 Tanjung Mutiara which were 33 students. Data collection instruments used was observation sheets, field notes, and knowledge (Cognitive) and skills (Psychomotor) test results. The results of this study indicate that learning using audiovisual media succeeded in improving the learning outcomes of 7th-grade students of SMP Negeri 2 Tanjung Mutiara. It is proved by the improvement of student learning outcomes in cycle I and cycle II where there is a very good improvement. In the first cycle, the results of the skills test (psychomotor) were 65.15%. As well as the results of the first cycle test for knowledge (cognitive) tests for learning outcomes the test showed 60.76%. Cycle II of learning test results on the skills test (psychomotor) is 82.42%. As well as the second cycle test for knowledge (cognitive) is 80.45%. Thus the use of audiovisual media improves learning outcomes in dance art learning in 7th-grade students of SMP Negeri 2 Tanjung Mutiara very well. Keywords: Increases, Learning Results, Dance, Audio Visual Media